Tourism, Culture and Regeneration - Smith, Melanie K (CABI, 2014)
The decision to edit this volume was prompted by a number of factors. A fascination with the increasingly prominent phenomenon of cultural regeneration seemed like a logical progression from earlier work undertaken in the field of cultural tourism (e.g. Smith, M.K. (2003) Issues in Cultural Tourism Studies. Routledge, London.). One small chapter in that publication hardly seemed to do justice to the diversity of projects that have been developing on a global scale in recent years. The government agenda in the UK and a large number of other countries worldwide has been focused on the potential of regeneration to transform cities. Whilst it is certainly not a panacea, it is exciting to watch relatively unknown and under-visited cities being transformed into well-known centres for culture, leisure and tourism. I knew that once I started choosing to holiday in former industrial rather than traditional historic cities, my interest in regeneration had gone way beyond academic! Cultural regeneration is a diverse and exciting subject for academic research, as well as being a challenging field for practitioners. My own PhD work has been testimony to that. It is multidisciplinary and requires holistic or joined-up thinking. No one field can claim to ‘own’ this subject as it arguably sits equally comfortably in urban studies, planning, architecture, cultural geography or sociology. One can also draw upon cultural studies, anthropology, economics, environmental studies, leisure and tourism, heritage studies (and more) to shed further light on the complexity of the phenomenon. The fact that the subject is in its relative infancy means that many of the issues are still open to debate, but the sharing of good practice through interesting and innovative case studies can help to disseminate knowledge. This volume therefore aims to contribute further to the latest discussions about cultural regeneration (theoretical and academic, as well as practitioner dilemmas), in addition to providing examples of contemporary practice. It was thought that a single-authored text could not do justice to the range of contexts, case studies and perspectives that could be encompassed in an edited volume. I am therefore grateful to the diverse range of authors for their valuable contributions to this project